Reduction of the environmental impact of aviation via optimisation of aircraft size/range and flight network. Issue 1 (1st February 2022) - Rötger, T; Casas, G; Çelikel, A; Dörries, H; Lim, L; Owen, B; van Velzen, A; Linke, F; Lührs, B; Lutz, M; Radhakrishnan, K
Abstract: REIVON is a Clean Sky 2 Technology Evaluator project that investigates to what extent CO2 emissions of global aviation can be reduced via optimisation of aircraft size/range and flight network. Three alternative global flight networks are created, considering (1) splitting long-haul flights into shorter legs (intermediate stop operations, ISO), (2) reducing frequency to the necessary minimum on busy routes using larger aircraft, and (3) a combination of 1 and 2. In all cases, the use of aircraft optimised for specific combinations of range and seating capacity not existing today will be considered. For the first time, REIVON will carry out a holistic analysis of the impact of an optimised flight network on global air transport system stakeholders, such as passengers, aircraft manufacturers, airlines and airports, and of potential measures to support the implementation of such an alternative network.